POST OPERATIVE ANALGESIA - Elangovan, Nandakumar; Dhanalakshmi; Nazar, Nabeel; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
AIM AND OBJECTIVE: To do a review on post-operative analgesia. BACKGROUND: The concept of analgesia is to reduce the magnitude and duration of the post-operative pain. Post-operative pain is one of the most frequently reported symptoms. The identification of the predictive factors is to facilitate early intervention and better pain management. Analgesic treatment is important to obtain efficient reduction of post-injury pain hypersensitivity. The development of safe and short-acting anesthetics, improved pain relief by early intervention with multimodal analgesia, and stress reduction by regional anesthetic techniques, β-blockers, or glucocorticoids have provided important possibilities for enhanced recovery. When these techniques are combined with a change in preoperative care, enhancement of recovery and decrease in hospital stay can be achieved, even in major operations. REASON: The reason is to gain current knowledge on post-operative analgesia.